Sistem Informasi Pendaftaran Siswa Baru pada SMA Negeri 1 Glumpang Tiga Kabupaten Pidie - Darmawan; Fathurrahmad; Abdus Salam (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2023)
Currently, not many schools in Indonesia have implemented online New Student Admissions (PSB). With the existing benefits and conveniences, this system should have been developed by each school. This is in line with advances in information and communication technology such as internet and web technology which are able to support the process of input and output data quickly and accurately, especially in the implementation of PSB. The limitation of the problem is only the Information System for New Student Registration Online at SMA Negeri 1 Glumpang Tiga, Pidie Regency. the purpose of the discussion, namely; to find out the Information System for Online New Student Registration at SMA Negeri 1 Glumpang Tiga, Pidie Regency and to design an Information System Application for New Student Registration Online at SMA Negeri 1 Glumpang Tiga, Pidie Regency. The author collects data with several data collection methods, including field studies and literature studies. Based on the results of observations and the authors can draw a conclusion which includes; The use of the Online New Student Registration Information System at SMA Negeri 1 Glumpang Tiga, Pidie Regency is expected to help create accurate and effective new student information data and with the existence of an information system it makes it easy for SMA Negeri 1 Glumpang Tiga, Pidie Aceh Regency because it speeds up information in general and reduce errors.